Imprints and DPPA3 are bypassed during pluripotency- and differentiation-coupled methylation reprogramming in testicular germ cell tumors - Killian, J. Keith; Dorssers, Lambert C.J.; Trabert, Britton; Gillis, Ad J.M.; Cook, Michael B.; Wang, Yonghong; Waterfall, Joshua J.; Stevenson, Holly; Smith, William I.; Noyes, Natalia; Retnakumar, Parvathy; Stoop, J. Hans; et al.

(untitled) (Genome Research, 2016)
Testicular germ cell tumors (TGCTs) share germline ancestry but diverge phenotypically and clinically as seminoma (SE) and nonseminoma (NSE), the latter including the pluripotent embryonal carcinoma (EC) and its differentiated derivatives, teratoma (TE), yolk sac tumor (YST), and choriocarcinoma. Epigenomes from TGCTs may illuminate reprogramming in both normal development and testicular tumorigenesis. Herein we investigate pure-histological forms of 130 TGCTs for conserved and subtype-specific DNA methylation, including analysis of relatedness to pluripotent stem cell (ESC, iPSC), primordial germ cell (PGC), and differentiated somatic references. Most generally, TGCTs conserve PGC-lineage erasure of maternal and paternal genomic imprints and DPPA3 (also known as STELLA); however, like ESCs, TGCTs show focal recurrent imprinted domain hypermethylation. In this setting of shared physiologic erasure, NSEs harbor a malignancy-associated hypermethylation core, akin to that of a diverse cancer compendium. Beyond these concordances, we found subtype epigenetic homology with pluripotent versus differentiated states. ECs demonstrate a striking convergence of both CpG and CpH (non-CpG) methylation with pluripotent states; the pluripotential methyl-CpH signature crosses species boundaries and is distinct from neuronal methyl-CpH. EC differentiation to TE and YST entails reprogramming toward the somatic state, with loss of methyl-CpH but de novo methylation of pluripotency loci such as NANOG. Extreme methyl-depletion among SE reflects the PGC methylation nadir. Adjacent to TGCTs, benign testis methylation profiles are determined by spermatogenetic proficiency measured by Johnsen score. In sum, TGCTs share collective entrapment in a PGC-like state of genomic-imprint and DPPA3 erasure, recurrent hypermethylation of cancer-associated targets, and subtype-dependent pluripotent, germline, or somatic methylation.